The PENGEMBANGAN MEDIA PRAKTIKUM BSD (Basic Solution Dilution) BERBASIS ANDROID MENGGUNAKAN TEKNOLOGI AI (Artificial Intelligence) PADA MATERI PENGENCERAN LARUTAN : PENGEMBANGAN MEDIA PRAKTIKUM BSD (Basic Solution Dilution) BERBASIS ANDROID MENGGUNAKAN TEKNOLOGI AI (Artificial Intelligence) PADA MATERI PENGENCERAN LARUTAN - Uliyandari, Mellyta Mellyta; Primairyani, Ariefa (University of Bengkulu, 2023)
The purpose of this research is to develop an Android-Based BSD (Basic Solution Dilution) practicum media using AI (Artificial Intelligence) Technology in solution dilution material. The development in this study was carried out with a 4D (four-D) define, design, develop, and disseminate. At the definition stage, the formulation of the practicum objectives is carried out, the design stage is carried out by designing the practicum media, while at the development stage the practicum media content validation is carried out by media experts and material experts, the dissemination stage is carried out via youtube. The results showed that the BSD practicum media was feasible to use, this was based on the validation results from two validators, namely material experts and media experts. The practicum media validation score by material experts is at number 69 which is in the